Hypertension, Sodium and Their Relationship among Adults or Middle-Aged Adults: A Scoping Review - Aisyah Desfiani Putri; Andi Putri Niswatu Syakirah; Almira Sitasari; Tri Siswati (Health Dynamics, 2024)
Background: Hypertension is expected to reach 60% by 2025, largely in low- and middle-income countries, with 46% unaware and 42% undiagnosed and untreated Knowing the intricate association between salt and adult hypertension is vital for public health efforts. This scoping review explain how sodium affects blood pressure to prevent hypertension in adults and middle-aged people. Methods: Tricco and colleagues' approach was used to examine hypertension and salt in adults and middle-aged people. Assessment techniques, hypertension prevalence, and sodium-hypertension relationships were reviewed. A comprehensive PubMed and Google Scholar search of full-text academic journals spanning 2013-2023 found relevant studies. Two researchers extracted data separately and reached consensus for eligible trials. The search phrases were hypertension, salt, adult, middle-aged, and young adult. Results: There were 13 articles, found that nutritional intake evaluations, 24-hour urine collections, clinical and laboratory tests, physical measurements, blood pressure monitoring, and specific trials or interventions are assessment methods. Salt consumption and hypertension show different prevalence rates. Conclusion: These studies also describe the complex relationship between salt intake and hypertension in adults and middle-aged people. These studies effectively elucidate a complex correlation between salt consumption and hypertension among middle-aged and adult individuals, notwithstanding variations in measurement approaches and prevalence.